PERSPEKTIF SISWA TERHADAP VIDEO ZELYNAFAH PADA PEMBELAJARAN PRONUNCIATION - Nadila, Nadila; Ismu Purwaningsih, Dewi; Yolanda, Alvina (Pengelola Jurnal Politeknik Negeri Ketapang, 2024)
The purpose of the research is descriptive qualitative to explore and describe the perspectives of class IX students at Smpi Darudda’wah Punggur Kecil on using the TikTok account @zelynafah’s videos for learning pronunciation. The study included 21 students, utilizing the questionnaires and interviews as research instruments. Nine statements were provided in the questionnaire, and interviews with 10 students were conducted using five questions. The findings indicate that students have a positive perspective on using @zelynafah’s TikTok videos to enhance their pronunciation skills.